Evaluation of the Antibacterial Effects of Nickel Nanoparticles on Biofilm Production by Streptococcus mutans - Nazanin Habibi (Journal of Medical Bacteriology, 2017)
Background:    Dental caries is a biofilm-dependent disease mainly causes by cariogenic bacteria that colonize dental surfaces, especially Streptococcus mutans. Nickel is a safe metal element which routinely used in dental compounds. The antibacterial and anti-biofilm effects of nickel nanoparticles (Ni-NPs) have been determined in limited studies, but the anti-biofilm effects of Ni-Nps on S. mutans have not been investigated before, so this study was aimed to investigate the anti-biofilm effects of Ni-NPs on S. mutans ATCC 35668.